Effect of Gene Mutation on Seizures in Surgery for Tuberous Sclerosis Complex. (28th May 2021) - Chivukula, Srinivas; Modiri, Omeed; Kashanian, Alon; Babayan, Diana; Ibrahim, George M.; Weil, Alexander G.; Tu, Albert; Wu, Joyce Y.; Mathern, Gary W.; Fallah, Aria
ABSTRACT: Background: Tuberous sclerosis complex (TSC) is a rare genetic disorder that commonly leads to drug-resistant epilepsy in affected patients. This study aimed to determine whether the underlying genetic mutation (TSC1 vs. TSC2) predicts seizure outcomes following surgical treatments for epilepsy. Methods: We retrospectively assessed TSC patients using the TSC Natural History Database core registry. Data review focused on outcomes in patients treated with surgical resection or vagus nerve stimulation. Results: A total of 42 patients with a TSC1 mutation, and 145 patients with a TSC2 mutation, were identified. We observed a distinct clinical phenotype: children with TSC2 mutations tended to be diagnosed with TSC at a younger age than those with a TSC1 mutation ( p < 0.001), were more likely to have infantile spasms ( p < 0.001), and to get to surgery at a later age ( p = 0.003). Among this TSC2 cohort, seizure control following resective epilepsy surgery was achieved in less than half (47%) the study sample. In contrast, patients with TSC1 mutations tended to have more favorable postsurgical outcomes; seizure control was achieved in 66% of this group. Conclusion: TSC2 mutations result in a more severe epilepsy phenotype that is also less responsive to resective surgery. It is important to consider this distinct clinical disposition when counseling families preoperatively with respect to seizure freedom. Larger samples are required to better characterize the independent effects of genetic mutation, infantile spasms, and duration of epilepsy as they relate to seizure control following resective or neuromodulatory epilepsy surgery.